Swift heavy ion track formation in SrTiO3 and TiO2 under random, channeling and near-channeling conditions. (21st April 2017) - Karlušić, M; Jakšić, M; Lebius, H; Ban-d'Etat, B; Wilhelm, R A; Heller, R; Schleberger, M
Abstract: Conditions for ion track formation in single crystal SrTiO3 and TiO2 (rutile) after irradiations using swift heavy ion beams with specific energies below 1 MeV/amu were investigated in this work. Rutherford backscattering spectroscopy in channeling was used to measure ion tracks in the bulk, while atomic force microscopy was used for observation of ion tracks on the surfaces. Variations in the ion track sizes and respective thresholds were observed after irradiations under random, channeling and near-channeling conditions close to normal incidence. These variations are attributed to the specifics of the electronic stopping power of swift heavy ions under the investigated conditions. In the case of ion channeling, electronic stopping power is reduced and observed ion tracks are smaller. The opposite was found under the near-channeling conditions when lowering of the ion track formation threshold was observed. We attribute this finding to the oscillating electronic stopping power with large peak values. For both materials, thresholds for bulk and surface ion track formation were found to be surprisingly close, around 10 keV nm −1 . Obtained results are compared with predictions of the analytical thermal spike model.